Room temperature ferromagnetism in Mn, N codoped ZnO thin films prepared by hydrothermal synthesis. (January 2014) - Shanthi, S.; Muthukumarasamy, N.; Agilan, S.; Balasundaraprabhu, R.
<x content-type="archive" xml:space="preserve">Abstract</x> Doping of Mn and N in ZnO results in p type ZnO. In the present study, hydrothermal method has been used to prepare Mn, N codoped ZnO nanorod thin films with hexagonal wurtzite structure. X-ray diffraction and X-ray photoelectron spectroscopy studies indicate that divalent Mn2+ ions are incorporated into ZnO lattice. The X-ray diffraction data further show that the prepared Mn, N codoped ZnO thin films have mainly a c axis oriented ZnO structure on the sapphire substrate. The surface morphology has been studied using a scanning electron microscope. The magnetic studies reveal that a high value of magnetisation is obtained when the magnetic field is applied parallel to the sample. The mechanism of ferromagnetic coupling in Mn, N codoped ZnO is discussed. The room temperature ferromagnetism present in the Mn, N codoped ZnO nanorods makes them potential candidate for spintronic applications.